"Bilingualism's Multifaceted Impact on Language Acquisition and Sociolinguistic Competence" (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
The article deals with the complex and dynamic influence of bilingualism on language learning and social interactions. With the growing prevalence of bilingualism in today's globalized world, it is essential to explore its various perspectives and trends. This article presents different viewpoints on bilingualism, encompassing cognitive, cultural, and societal dimensions. It highlights the significance of current trends, such as code-switching, heritage language maintenance, and language policies, in shaping bilingual individuals' experiences.